Pengaruh Profitabilitas, Solvabilitas, dan Ukuran Perusahaan terhadap Audit Delay pada Perusahaan Energi yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2025 - Sulistia Wati; Dyah Shinta Kusumaningtyas; Nova Herdina (Journal of Management and Creative Business, 2026)
This study aims to analyze the effects of Profitability, Solvency, and Company Size on Audit Delay in energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2025 period. This study employs a quantitative approach using secondary data from annual financial reports obtained from the official IDX website. The sample consists of 28 companies selected through purposive sampling, resulting in 112 observations over four years. Data were analyzed using multiple linear regression, t-test, F-test, and the coefficient of determination (Adjusted R²), following classical assumption tests conducted using IBM SPSS Statistics version 29. The results show that Profitability has a negative and significant effect on Audit Delay, while Solvency has a positive and significant effect. Company Size has no significant effect on Audit Delay. Simultaneously, the three variables significantly affect Audit Delay. The Adjusted R² value of 7.9% indicates that the model explains 7.9% of the variation in Audit Delay, while the remaining 92.1% is influenced by other factors outside the research model.